Simultaneous sulfur dioxide and mercury removal during low-rank coal combustion by natural zeolite. Issue 5 (May 2021) - Gani, Asri; Wattimena, Yuanda; Erdiwansyah,; Mahidin,; Muhibbuddin,; Riza, Medyan
Abstract: Sulfur dioxide (SO2 ) and trace metal such as mercury emission during combustion of low-rank coal cause a significant impact on the environment and health. Flue gas at coal-fired power stations is one of the main sources for the emissions of SO2 and mercury metal. Low-cost and sustainable technologies for the removal of SO2 and mercury from flue gas have become increasingly important nowadays. This paper presents the study of simultaneous removal of SO2 and mercury over natural zeolite as an adsorbent in briquette and pulverized. The research is focused on evaluating adsorbent to coal optimum ratio towards adsorption performance on SO2 and mercury removal. The experiments on the removal of SO2 and mercury were carried out using horizontal electric furnace with different combustion temperature and adsorbent ratio. SO2 in the flue gas as the result of the combustion process which exits from the outlet was analyzed using Gas Combustion and Emission Analyzer (E4400, E-Instrument). Mercury metal residues in the bottom ash were analyzed using NIC Mercury SP Analyzer. An increasing zeolite adsorbent SO2 content in flue gas decreased. The optimum SO2 removal was determined on 4% zeolite adsorbent ratio. It also has been found that 8% natural zeolite ratio to low-rank coal show optimum condition to adsorb mercury for all temperature condition for both briquette and pulverized conditions. Abstract : Sulphur dioxide, Mercury removal, Combustion, Natural zeolite, Adsorbent